2018
DOI: 10.1109/tvcg.2018.2868581
|View full text |Cite
|
Sign up to set email alerts
|

PizzaText: Text Entry for Virtual Reality Systems Using Dual Thumbsticks

Abstract: We present PizzaText, a circular keyboard layout technique for text entry in virtual reality (VR) environments that uses the dual thumbsticks of a hand-held game controller. Text entry is a common activity in VR environments but remains challenging with existing techniques and keyboard layouts that is largely based on QWERTY. Our technique makes text entry simple, easy, and efficient, even for novice users. The technique uses a hand-held controller because it is still an important input device for users to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…Many studies have focused on text input using other input devices. PizzaText [38], TwoStick [39], and Sandnes [40] used a hand-held game controller to input text by multiple step confirmation. The entry speed of novices on PizzaText was 8.59 WMP after two hours of training, while that of experts could reach 15.85 WMP.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have focused on text input using other input devices. PizzaText [38], TwoStick [39], and Sandnes [40] used a hand-held game controller to input text by multiple step confirmation. The entry speed of novices on PizzaText was 8.59 WMP after two hours of training, while that of experts could reach 15.85 WMP.…”
Section: Related Workmentioning
confidence: 99%
“…Users should easily carry the device, and wearable devices ensure portability. Therefore, products that are inconvenient for users to carry or require help from other people (for example, tablet handwriting input [6] and game controller input [38,39,40]) are not very suitable.…”
Section: Design Principlesmentioning
confidence: 99%
“…In our experiments, we showed that our prototype is competitive with commercial smartwatches in its size while input events are generated responsively (55-61 ms) and accurately. We believe our approach can be useful in VR entertainment and games scenarios for using the smartwatch as an effective controller when coupled with an HMD [30,33,34]. Especially for a cross-device ecology where multiple devices are seamlessly connected [35], our approach may serve as a cohesive single interaction device to enable various cross-device interaction scenarios and applications at different scales for near, personal, social and public levels [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previously joysticks are mostly used in gaming context for selecting certain targets using a game controller analog thumbstick [28]. Other uses of joysticks include issuing driving commands for wheelchairs [29] and text entry in VR systems [30]. Usability and UX aspects of the joystick-embedded UI and other wearable UIs are thoroughly examined in [27].…”
Section: Iterative Prototyping Of Joystick-based Wearable User Interfacementioning
confidence: 99%
“…HiPad [30] uses the circular touchpad on a common VR controller to select characters laid out in a circle. PizzaText [61] similarly uses a pair joysticks (as on a modern game console controller). One joystick selects a 'slice' of four characters, and the other designates which character to choose within the slice.…”
Section: Gesture and Controller Vr/ar Text Inputmentioning
confidence: 99%